Cardiomyocyte differentiation from mouse embryonic stem cells using a simple and defined protocol. Issue 2 (27th November 2015) - Kokkinopoulos, Ioannis; Ishida, Hidekazu; Saba, Rie; Coppen, Steven; Suzuki, Ken; Yashiro, Kenta
Abstract : Background: Embryonic stem (ES) cells are pluripotent cells with the ability to differentiate to any cell type of the resident organism. In recent years, significant advances have been made in using these cells to obtain large numbers of cardiomyocyte (CM) ‐like cells for scientific research and clinical application. A vast number of protocols have emerged describing differentiation methods without the use of animal serum or extracts restrictive for use in a human clinical setting. These techniques follow a complicated procedure, which although successful, show a relatively varied yield among cell batches.Results: We have designed a three‐step differentiation protocol using defined reagents and a monolayer culture without feeder cells, avoiding embryoid body formation and multiple trypsin treatment, in which beating foci appeared as early as day 6 in in vitro differentiating conditions. Our results show a high yield of CM reaching approximately 60% of the differentiated cells after 13 days in vitro.Conclusions: We provide a fast, simple, reliable and reproducible protocol for inducing murine ES cells toward a CM‐like phenotype comparable to available high‐yield protocols, without the use of intermediate trypsinization/passage steps. Developmental Dynamics 245:157–165, 2016 . © 2015 Wiley Periodicals, Inc. Key Findings: Reproducible protocol of murine ES cells with high yield of cardiomyocyte-like cells. Differentiation accomplished via monolayer culture in serum-free conditions. Consistent >30% cardiomyocyte-like cell enrichment. Rapid beating foci appearance.